2015
DOI: 10.1111/ijcs.12244
|View full text |Cite
|
Sign up to set email alerts
|

What is going on when nothing is going on? Exploring the role of the consumer in shaping waiting situations

Abstract: Research on waiting in services focuses mainly on the role of companies in waiting situations. Much of the existing research envisages the consumer as a passive victim of the delays caused by companies. This article redresses the imbalance in research on waiting by exploring the role of consumers in waiting situations. A qualitative methodology is used, involving data collection through in‐depth interviews and personal diaries, to facilitate an in‐depth analysis of consumers’ waiting experiences. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 74 publications
(126 reference statements)
0
9
0
Order By: Relevance
“…Previous studies [8] have already shown the importance of reducing waiting times for companies, as this is a factor with the potential to greatly compromise the consumer's shopping experience.…”
Section: Mobile Payment As a Tool For Digital Transformationmentioning
confidence: 99%
“…Previous studies [8] have already shown the importance of reducing waiting times for companies, as this is a factor with the potential to greatly compromise the consumer's shopping experience.…”
Section: Mobile Payment As a Tool For Digital Transformationmentioning
confidence: 99%
“…There are fascinating studies of what people do in queues to reduce their frustration (Pamies, Ryan, & Valverde, 2016). All sorts of factors influence how people react to queues.…”
Section: The Academic Literaturementioning
confidence: 99%
“…In other words, the act of joining a queue can help co-create values. Similarly, a long queue can be regarded as a collection of endorsements of quality and value assurance (Koo and Fishbach, 2010; Pàmies et al , 2016a; Veeraraghavan and Debo, 2009), and thus help increasing consumers’ satisfaction and purchase intention (Giebelhausen et al , 2011).…”
Section: The Power Of the Queue: Queue=cuementioning
confidence: 99%
“…Consumers of different segments can read into the lines quite differently. When consumers interpret queues favorably, waiting in lines can result in positive effects for both consumers and companies (Giebelhausen et al , 2011; Koo and Fishbach, 2010; McGuire et al , 2010; Pàmies et al , 2016a). For example, the phenomena that people repeatedly line up for days in advance to obtain certain newly launched products, such as iPhone X, PlayStation 4 and Nintendo Switch, constitute evidence that a long line can help promote new products among loyal consumers, while non-loyal consumers may not share the same enthusiasms (Frum, 2013; Kain, 2017; Price, 2017).…”
Section: Introductionmentioning
confidence: 99%